The tip of the iceberg: extraordinarily high diversity while examining two infralittoral nematode communities on Okinawa-jima Island, Japan, using morphology and DNA barcoding - Marilyn Carletti; Nuria Viñuela Rodríguez; Gaia Rossetti; Virginia Rossi; Bryan Gabriel Pulido Tan; James Davis Reimer (PeerJ)
Background Nematodes are among the most diverse and abundant metazoans in aquatic habitats, contributing significantly to global biodiversity. Despite their abundance and importance, the presumed number of undescribed species is high and their diversity is often underestimated. Methods In this research, sediment samples were collected from three microhabitats (bare sand, seagrass, coral) in two sites around Okinawa-jima Island in subtropical southern Japan. Nematode specimens were obtained by filtering the sediment and were then used to determine meiofaunal assemblages with morphology and molecular methods at the two sites and to compare them with environmental variables. Results The results showed an overwhelmingly high biodiversity of nematofauna with both methods. The morphological identification of free-living nematodes was partly supported by molecular analyses, with the results varying more regarding less common taxa. The discrepancies between different methods may be due to low success of DNA amplifications, high nucleotide variability, and overestimation of congeneric specimens. We observed that coral reef habitats clearly differed from nearby sand and seagrass beds in terms of nematode genus-level assemblages. We identified at least 10 orders and 38 genera of nematodes from our samples that only span two different sites, and it is highly likely these samples include undescribed taxa. Our results strongly suggest that coral reefs and neighboring areas are hot-spots for nematode diversity, at least around Okinawa-jima Island if not also in other coral reef regions.